Study of muonium emission from laser-ablated silica aerogel. (21st September 2020) - Beare, J; Beer, G; Brewer, J H; Iijima, T; Ishida, K; Iwasaki, M; Kamal, S; Kanamori, K; Kawamura, N; Kitamura, R; Li, S; Luke, G M; et al.
Abstract: The emission of muonium (μ^+e^- ) atoms into vacuum from silica aerogel with laser ablation on its surface was studied with various ablation structures at room temperature using the subsurface muon beams at TRIUMF and Japan Proton Accelerator Research Complex (J-PARC). Laser ablation was applied to produce holes or grooves with typical dimensions of a few hundred μ m to a few mm, except for some extreme conditions. The measured emission rate tends to be higher for larger fractions of ablation opening and for shallower depths. More than a few ablation structures reach the emission rates similar to the highest achieved in past measurements. The emission rate is found to be stable at least for a couple of days. Measurements of spin precession amplitudes for the produced muonium atoms and remaining muons in a magnetic field determine a muonium formation fraction of (65.5 ± 1.8) %. The precession of the polarized muonium atoms is also observed clearly in vacuum. A projection of the emission rates measured at TRIUMF to the corresponding rates at J-PARC is demonstrated taking the different beam condition into account reasonably.